2020
DOI: 10.1302/2046-3758.95.bjr-2019-0213.r1
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a rapid lateral flow calprotectin test for the diagnosis of prosthetic joint infection

Abstract: Aims This pilot study tested the performance of a rapid assay for diagnosing prosthetic joint infection (PJI), which measures synovial fluid calprotectin from total hip and knee revision patients. Methods A convenience series of 69 synovial fluid samples from revision patients at the Norfolk and Norwich University Hospital were collected intraoperatively (52 hips, 17 knees) and frozen. Synovial fluid calprotectin was measured retrospectively using a new commercially available lateral flow assay for PJI diagnos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Four studies were removed by scanning titles and abstracts. After reading the full text in detail, the meta-analysis included 7 studies finally [ 19 , 21 26 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were removed by scanning titles and abstracts. After reading the full text in detail, the meta-analysis included 7 studies finally [ 19 , 21 26 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that calprotectin can promote inflammation reaction and is regarded as the detection of inflammatory markers for rheumatoid arthritis (RA), inflammatory bowel disease (IBD), and spondyloarthritis [ 15 18 ]. Recent follow-up studies suggest that the synovial calprotectin was a useful biomarker for the diagnosis of PJI [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synovial calprotectin studies. Five studies described the diagnostic accuracy of synovial fluid PCR in the detection of PJI, [38][39][40][41][42] using the msis criteria as the standard reference test, with baseline characteristics of individual studies shown in table iv. the overall sensitivity was 0.94 (95% CI 0.82 to 0.98), specificity was 0.93 (95% ci 0.85 to 0.97), Plr was 13.2 (95% ci 5.7 to 30.6), nlr was 0.07 (95% ci 0.02 to 0.21), and dOr was 191 (95% ci 32 to 1,157).…”
Section: Resultsmentioning
confidence: 99%
“…additionally, of the five studies included in the calprotectin group, three used laboratory-based immunoassays, 38,39,42 whereas the remaining two used lateral flow testing. 40,41 Despite these differences, there was no significant heterogeneity between studies. Furthermore, there was a lack of inclusion of multiple other biomarkers, such as serum ESR, serum CRP, synovial fluid alpha-defensin, and synovial fluid CRP.…”
Section: Discussionmentioning
confidence: 99%
“…Calprotectin, also known as cystic fibrosis antigen, is a protein complex mainly secreted by neutrophils as part of the inflammatory response and plays a role in leukocyte migration and stimulation [9]. Different testing methods have also been explored to detect synovial Calprotectin, including enzyme-linked immunosorbent assay (ELISA) and lateral flow testing, showing promising results [10,11]. Several studies have reported the efficacy of synovial Calprotectin in the diagnosis of PJI; however, further understanding of the underlying pathophysiology and diagnostic accuracy is warranted.…”
Section: Introductionmentioning
confidence: 99%